2016
DOI: 10.1038/nchembio.2125
|View full text |Cite
|
Sign up to set email alerts
|

Pistol ribozyme adopts a pseudoknot fold facilitating site-specific in-line cleavage

Abstract: The field of small self-cleaving nucleolytic ribozymes has been invigorated by the recent discovery of the twister, twister-sister, pistol and hatchet ribozymes. We report on the crystal structure of the env25 pistol ribozyme, which adopts a compact tertiary architecture stabilized by an embedded pseudoknot fold. The G-U cleavage site adopts a splayed-apart conformation with in-line alignment of the modeled 2′-O of G for attack on the adjacent to-be-cleaved P-O5′ bond. Highly conserved residues G40 (N1 positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
190
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(209 citation statements)
references
References 43 publications
15
190
1
1
Order By: Relevance
“…The pH dependence of this ribozyme is similar to that of the hammerhead. The overall structure is reminiscent of that of the hammerhead (23,25), and the structure of the active center is consistent with a role for a guanine N1 and an O2' as general acid. This requires more detailed mechanistic investigation.…”
Section: The Hammerhead Ribozyme -The Role Of a 2'-hydroxyl Groupmentioning
confidence: 65%
See 1 more Smart Citation
“…The pH dependence of this ribozyme is similar to that of the hammerhead. The overall structure is reminiscent of that of the hammerhead (23,25), and the structure of the active center is consistent with a role for a guanine N1 and an O2' as general acid. This requires more detailed mechanistic investigation.…”
Section: The Hammerhead Ribozyme -The Role Of a 2'-hydroxyl Groupmentioning
confidence: 65%
“…There are now nine distinct members of this group. Crystal structures have now been determined for the majority of these ribozymes (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The reaction is initiated when an O2' atom attacks the adjacent phosphorus in an SN2 transesterification reaction leading to the formation of a 2'3'-cyclic phosphate and a 5' hydroxyl group (Figure 1).…”
Section: The Nucleolytic Ribozymesmentioning
confidence: 99%
“…The superposition of the active sites yields an rmsd = 0.494 Å (Fig. S3 A and C) (20), indicating that the overall structure and active site are similar and within experimental error. The main difference between the two active site conformations is that nucleotide 32 is a guanine in our structure, whereas it is an adenosine in the structure of Pistol Env.25 reported by Ren et al (20).…”
mentioning
confidence: 99%
“…Based on the recent biochemistry results, it has been suggested that the purine base at position 32 is the likely candidate to serve as the general acid for donating a hydrogen to the leaving O5′. Mutagenesis studies have shown that the Pistol self-cleavage activity is 100% in 10 min with an A32G mutation, whereas activity was abolished when the A32 N3 atom was substituted by a carbon atom (20). Furthermore, the pK a of the A32 N3 atom was found to be shifted up by 1 pH unit to 4.7, which suggests that the A32 N3 atom has an increased chance of being protonated, even under physiological pH (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation